Peranan Pengadilan Agama Dalam Penyelesaian Sengketa Perdata Islam: Analisis Putusan Kontemporer - Rihana Hidayanti; Freska Salsabila; Riezka Nurhidayati; Asrizal Saiin; Asrizal (Institut Agama Islam Negeri Metro, 2025)
Abstract: Religious Courts have a strategic role in resolving Islamic civil disputes in Indonesia, especially in family, inheritance, and sharia economic cases. This article analyzes the role of Religious Courts through contemporary decisions that show adaptation to legal developments and social dynamics. In divorce disputes, the latest decisions consider aspects of gender justice and child protection. In inheritance cases, several decisions provide more flexible interpretations for the sake of social justice. Meanwhile, in sharia economic disputes, Religious Courts increasingly consider the principle of contractual justice. The results of the analysis show that Religious Courts not only play a role as enforcers of Islamic law, but also as institutions that adjust decisions to developments in society. Keywords: Religious Courts, Islamic Civil Disputes, Islamic Family Law.